EFEKTIVITAS PEMBELAJARAN KARAWITAN MENGGUNAKAN MEDIA GAMELAN DIGITAL: STUDI KASUS KELAS 10 SMA NEGERI 6 SURAKARTA - Novaldi Bayu Nurholis Hadi Syahputra; Denis Setiaji (TAMUMATRA, 2025)
The limited availability of gamelan facilities in secondary schools makes the process of teaching karawitan unable to run optimally, thus requiring digital technology–based innovations to support practical activities. To address this challenge, the presence of the Virtual Gamelan application offers an alternative approach to karawitan learning that is more interactive and flexible, as it can be accessed anytime and anywhere. Through this application, students can learn to play gamelan, memorize learning materials, practice skills, and express themselves more easily. However, the implementation of the Virtual Gamelan application in the learning process also faces various obstacles, both technical and pedagogical. This study aims to analyze the ease of use, the challenges encountered, and the level of effectiveness of the Virtual Gamelan application during the learning process. In addition, this study identifies the factors that influence the application’s effectiveness as a learning medium. The method used is a qualitative approach with a case study focused on the use of the E-Gamelan and Gamelan JV applications in traditional music learning for 10th-grade students at SMA Negeri 6 Surakarta. The results show that the use of the Virtual Gamelan application provides significant benefits in the learning process, particularly in enhancing student engagement and accessibility. Nevertheless, several aspects still need improvement to increase effectiveness and user experience. Overall, this application has great potential in supporting the preservation and learning of gamelan in the digital era. These findings affirm that the digitalization of gamelan through interactive applications has the potential to become an effective means for preserving and teaching traditional music in schools.